Prevalence and clinical significance of Claudin-3 expression in cancer: a tissue microarray study on 14,966 tumor samples - Seyma Büyücek; Nina Schraps; Anne Menz; Florian Lutz; Viktoria Chirico; Florian Viehweger; David Dum; Ria Schlichter; Andrea Hinsch; Christoph Fraune; Christian Bernreuther; Martina Kluth; et al. (Biomarker Research)
Abstract Background Claudin-3 (CLDN3) participates in the formation of the tight-junctions (TJs) that regulate intercellular permeability. Altered CLDN3 expression has been linked to tumor progression in multiple tumor types. Despite its widespread expression in normal epithelial cells, CLDN3 is considered an attractive drug target candidate, since it may be more accessible in cancer cells than in normal cells due to their less orchestrated cell growth. Methods To comprehensively determine the prevalence of CLDN3 expression in cancer, a tissue microarray containing 14,966 samples from 133 different tumor types and subtypes as well as 608 samples of 76 different normal tissue types was analyzed by immunohistochemistry. Results CLDN3 immunostaining was observed in 8,479 (68.9%) of 12,314 analyzable tumors, including 11.6% with weak, 6.2% with moderate, and 51.1% with strong positivity. CLDN3 staining was found in 96 of 133 tumor categories, 80 of which contained at least one strongly positive case. CLDN3 positivity was most seen in neuroendocrine neoplasms (92–100%) and in adenocarcinomas (67–100%), tumors of the female genital tract, including various subtypes of ovarian and endometrial carcinoma (up to 100%), as well as different subtypes of breast cancer (95.3–100%). CLDN3 positivity was less common in squamous cell carcinomas (0–43.2%) and mainly absent in melanoma, mesenchymal, and hematolymphatic neoplasms. In clear cell renal cell carcinoma (ccRCC), low CLDN3 was strongly linked to poor ISUP (p < 0.0001), Fuhrman (p < 0.0001), and Thoenes (p < 0.0001) grades, advanced pT category (p < 0.0001), high UICC stage (p = 0.0006) and distant metastasis (p = 0.0011), as well as shortened overall (p = 0.0118) and recurrence-free (p < 0.0001) survival. In papillary RCC (pRCC), low CLDN3 was associated with poor grade (p < 0.05), high pT (p = 0.0273) and distant metastasis (p = 0.0357). In urothelial carcinoma high CLDN3 was linked to high grade (p < 0.0001) and nodal metastasis (p = 0.0111). The level of CLDN3 staining was unrelated to parameters of tumor aggressiveness in pancreatic, gastric, and breast cancer. Conclusion In conclusion, our data demonstrate significant levels of CLDN3 expression in many different tumor entities and identify reduced CLDN3 expression as a potential prognostic marker in RCC.